Long-Term Evolution of Inequality of Opportunity - Maurizio Bussolo; Daniele Checchi; Vito Peragine (Institute of Labor Economics (IZA), 2020)
The main goal of this paper is to document and analyze the long-term evolution of inequality of opportunity (IOp) in the four largest European economies (France, Germany, Great Britain and Italy). Relative IOp represents an important portion of total income inequality, with values ranging from 30 to 50 percent according to the standard deviation of logs. For all the countries, relative IOp shows a stable or declining time trend. In addition to these descriptive findings, the paper proposes a theoretical framework identifying channels of transmission which may affect IOp. Using this framework, a decomposition focuses on the role of three variables: a) intergenerational persistence in educational attainment, b) return of education, and c) networking activity of parents. While the first two variables exhibit a declining trend in all countries, which as predicted by the model should produce a decline in IOp, the third one appears to be rising in some countries, counteracting the effects of the first two.
Keywords: D31; D63; E24; I24; J62; 330; inequality of opportunity; decomposition methods; education mobility; returns to education; family networking